1998
DOI: 10.1021/jp982209t
|View full text |Cite
|
Sign up to set email alerts
|

Surface Characterization of Cu−M (M = Ti, Zr, or Hf) Alloy Powder Catalysts

Abstract: X-ray photoelectron spectroscopy was used for surface characterization of amorphous Cu−M alloy powders (Cu40Ti60, Cu50Zr50, and Cu65Hf35) produced by mechanical alloying of the constituents. When used as catalyst in the dehydrogenation of alcohols Cu−Zr and Cu−Hf were found to undergo structural changes resulting in surface copper enrichment with a substantial fraction of copper being in fully reduced, metallic (Cu0) state. This result accounts for the high and stable catalytic activity of Cu−Zr and Cu−Hf in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 38 publications
1
2
0
Order By: Relevance
“…The BE value obtained here is close to that reported by Espinos et al for dispersed CuO species supported on the zirconia (934.4 eV) . The peaks at 932.9 eV are characteristics for Cu 0 or Cu 2 O species. , Detection of a significant amount of Cu 0 or Cu + contradicts data from other methods. Observation of the reduced copper species probably results from photoreduction in the spectrometer, when X-ray radiation under the high vacuum environment affects removal of the labile oxygen species of highly dispersed copper(II) oxide clusters.…”
Section: Resultssupporting
confidence: 78%
“…The BE value obtained here is close to that reported by Espinos et al for dispersed CuO species supported on the zirconia (934.4 eV) . The peaks at 932.9 eV are characteristics for Cu 0 or Cu 2 O species. , Detection of a significant amount of Cu 0 or Cu + contradicts data from other methods. Observation of the reduced copper species probably results from photoreduction in the spectrometer, when X-ray radiation under the high vacuum environment affects removal of the labile oxygen species of highly dispersed copper(II) oxide clusters.…”
Section: Resultssupporting
confidence: 78%
“…To investigate the bonding configuration of samples, the XPS survey spectrum range of PHs, PHs‐SO 3 H and catalyst‐2 from 0 to 1000 eV (a) and the amplified spectra of S 2p (b) and Hf 4 f (c) were revealed, just as Figure shown. The spectras were shown in Figure a confirmed that all four samples show two main peaks at 286.6 eV and 530.4 eV corresponding to C 1 s and O 1 s . As shown in Figure b‐c, the peaks at about 170.61 eV and 20.59 eV could be singly regarded as S 2p and Hf 4 f. Correspondingly, the emerging signal of C 1s was connected with the C−S of these samples.…”
Section: Resultsmentioning
confidence: 55%
“…[17] Some coumarinyl triazoles, like compound 4b synthesized within this research, have already proven to possess a good antimicrobial activity against Klebsiella pneumonia and Aspergillus fumigates. [22] 1,2,4-Triazoles are often prepared from thiosemicarbazides, in basic conditions with sodium hydroxide [23][24][25] or trimethylamine, [26] as well as from 1,3,4-oxadiazoles and substituted hidrazides [27] or by reductive rearrangement of 1,2,4-oxadiazoles in reaction with hydrazine. [28] Azzouni et al synthesized 1,2,4-triazoles from acryloylimidates with hydrazines at room temperature in methanol, expanding the possibilities of introducing substituents in positions N(1), C(3) and C(5) of 1,2,4triazole ring.…”
Section: Introductionmentioning
confidence: 99%